2003
DOI: 10.1034/j.1399-3089.2003.02032.x
|View full text |Cite
|
Sign up to set email alerts
|

Intragraft cytokine mRNA expression in rejecting and non‐rejecting vascularized xenografts

Abstract: We hereby conclude that both AVR on day 2 and cell-mediated rejection on day 8 (under DSG treatment) in a concordant cardiac mouse-to-rat xenotransplantation model are associated with an increase of proinflammatory cytokines, T helper 1 (Th1)-associated cytokines as well as IL-10, while immunosuppression with CyA + DSG diminishes the levels of all examined cytokines. Grafts undergoing AVR or cellular rejection are subjected to deposits of both IgM and IgG, although circulating donor specific antibodies are und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The targets for those antibodies are not clearly identified. Some are probably also present on mouse blood cells because there are high titres of haemagglutinating and lymphocytotoxic antibodies present in the rat sera after rejection, as our previous study confirmed (14). Moreover, passive transfer of antierythrocyte or antilymphocyte sera shortly after transplantation induces hyperacute rejection (9).…”
Section: Discussionsupporting
confidence: 58%
“…The targets for those antibodies are not clearly identified. Some are probably also present on mouse blood cells because there are high titres of haemagglutinating and lymphocytotoxic antibodies present in the rat sera after rejection, as our previous study confirmed (14). Moreover, passive transfer of antierythrocyte or antilymphocyte sera shortly after transplantation induces hyperacute rejection (9).…”
Section: Discussionsupporting
confidence: 58%
“…One limitation of this approach in the experimental setting is that evaluation of composite EC-MSC islet grafts in small animal models are not easily performed because of several significant species-specific differences in important areas such as angiogenesis, tissue repair, and innate immunity (31). Also, severely immunodeficient mice (SCID, nu/nu, and Rag) trigger strong innate immune responses that mainly target the vasculature of a transplanted organ due to the phylogenetic disparity between the two species, i.e., human-to-mouse is a discordant xenotransplantation model triggering activation of neutrophils, natural killer cells, macrophages, the complement and coagulation systems, and naturally occurring xenoreactive antibodies (32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Whether IFN-␥ promotes or protects against xenograft rejection is unclear. A study by Wang et al (51) found that IFN-␥ together with IL-12 was protective against AHXR, whereas other studies have demonstrated that high levels of IFN-␥ are associated with rejection (52)(53)(54)(55). The precise role of IFN-␥ in xenotransplantation remains to be elucidated.…”
Section: ϫ/ϫmentioning
confidence: 99%